Conception & realization of a Smartwatch controlled by Android Smartphone - ALLAOUI KHADIDJA; Gueffaf, Hamza (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2020)
The goal of this project is to design a SmartWatch related to a Smartphone using an android application “Smart-Clock” that we’ve invent , we used in this design an Arduino Nano board after studying all the other boards we used the Nano board because of it suitability especially the size affect, then we identified the other different components necessary for the project, their characteristics, their method of connection and the programming method of each component including the OLED screen, the Bluetooth HC-06 and finally the power supply device, then the controlling program was accomplished by IDE using the C++ language
OPTION: Electronics of embedded systems